Pain reduction after total laparoscopic hysterectomy and laparoscopic supracervical hysterectomy among women with dysmenorrhoea: a randomised controlled trial1. (19th April 2015) - Berner, E; Qvigstad, E; Myrvold, AK; Lieng, M
<x xml:space="preserve">Abstract</x> Objective To evaluate the effectiveness of total laparoscopic hysterectomy compared with laparoscopic supracervical hysterectomy for alleviating dysmenorrhoea. Design Randomised blinded controlled trial. Setting Norwegian university teaching hospital. Sample Sixty‐two women with dysmenorrhoea. Methods Participants randomised to either total laparoscopic hysterectomy (n = 31) or laparoscopic supracervical hysterectomy (n = 31). Main outcome measures The primary outcome measure, measured 12 months after intervention, was reduction of cyclic pelvic pain (visual analogue scale, 0–10). Secondary outcome measures included patient satisfaction (visual analogue scale, 0–10) and quality of life (Short Form 36, 0–100). Results The groups were comparable at baseline. There was no difference in self‐reported dysmenorrhoea at 12 months (mean 0.8 [SD 1.6] versus 0.8 [SD 2.0], P = 0.94). There was no difference in patient satisfaction (mean 9.3 [SD 1.5] versus 9.1 [SD 1.2], P = 0.66) or quality of life (mean 81.6 [SD 17.8] versus 80.2 [SD 18.0], P = 0.69). Conclusion Improvement in dysmenorrhoea and quality of life as well as patient satisfaction were comparable in the medium term when comparing total laparoscopic hysterectomy with laparoscopic supracervical hysterectomy.